Photos that inspire photo workshop - Eodice, Lynne; Safari eBooks (Hoboken, N.J. : Wiley Pub., 2008)
"This unique book is packed with more than 200 magnificent photos, each expressing the photographer's unique take on a scene or subject. With each image, the artist shares a description of the setting, what inspired the idea, and what the photo was intended to accomplish, along with the technical details--camera and lens used, shutter speed, aperture, and lighting. Stimulate your creativity with these breathtaking landscapes, incredible action shots, heartwarming portraits of people and pets, intriguing close-ups, and more"--Resource description page.
Landscape, scenic and travel photography -- Animal and wildlife photography -- People and portrait photography -- Action, sports and motion photography -- Night, low light and magic hour photography -- Architecture and urban scenes -- Botanical photography -- Macro and close-up photography -- Still life photography -- Skin.
Description based on print version record.
Keywords: Photography -- Digital techniques; Photography, Artistic; Electronic books